2020
DOI: 10.1021/acs.langmuir.0c02372
|View full text |Cite
|
Sign up to set email alerts
|

Direct Measurement of Contact Angle Change in Capillary Rise

Abstract: Capillary rise is important in many aspects of physical phenomena from transport in porous media to biotechnology. It is typically described by the Lucas−Washburn−Rideal equation (LWRE), but discrepancy between some experiments and the model still remains elusive. In this paper, we show that the discrepancy is simply from the contact angle change during the capillary rise with no help of any specific models, such as dynamic contact angle (DCA) models. To demonstrate this, we directly measure the contact angle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…Even though there is evidence that in some cases meniscus formation and capillary rise may occur concurrently, it assumed here that they are two distinct stages. First, the meniscus fully forms, and then, the liquid rises in the tube.…”
Section: Theorymentioning
confidence: 92%
See 1 more Smart Citation
“…Even though there is evidence that in some cases meniscus formation and capillary rise may occur concurrently, it assumed here that they are two distinct stages. First, the meniscus fully forms, and then, the liquid rises in the tube.…”
Section: Theorymentioning
confidence: 92%
“…Since that time, many aspects of capillary rise have been experimentally measured and theoretically modeled for various types of tubes and liquids. Capillary rise has been examined in the absence of gravity, in tilted tubes, , in noncircular tubes, in tapered tubes, , in rough tubes, ,, between two tubes, in chemically heterogeneous tubes with wetting gradients, in tubes where viscous forces control the rate at which liquid rises, in tubes where the inertial forces of the liquid dominated over viscous forces, , and in tubes where the contact angle ,− or viscosity , depended on the rate of liquid rise.…”
Section: Introductionmentioning
confidence: 99%
“…The following designs are proposed and compared by the model to quantify the gas and liquid flow resistance within MEA. The capillary pressure of micro-meter-size pores is much higher than the liquid flow resistance, and the time scale for contact angle dynamics is on the order of 1-10 ms [26]. Therefore, the design principle is to reduce the liquid connection between the CL and the fuel channel.…”
Section: Designs Of Membrane Electrode Assembly Structures Tomentioning
confidence: 99%
“…However, this has recently been questioned in light of experimental results indicating that the contact angle is affected by the velocity of the contact line . Even though some authors ,, reported that, for several liquids, the predicted deviations from the classical Lucas–Washburn equation due to velocity-dependent contact angles are very small, several experimental studies , and theoretical investigations supported by numerical and experimental data , reported better agreement with models that included this effect than with Lucas–Washburn approaches. In the literature, different dynamic contact angle models can be found to predict the dynamic contact angle effects in the capillary imbibition process.…”
Section: Introductionmentioning
confidence: 99%